Peningkatan Motivasi dan Hasil Belajar Menemukan Gagasan Utama Paragraf Melalui Teknik Pembelajaran SQCP bagi Peserta Didik Kelas IX-B SMP Negeri 1 Jaken Semester Genap Tahun 2014/2015 - Suladi, Slamet (LP3 Universitas Negeri Semarang, 2015)
The outline for this PTK are how the learning process occur, enhancing learning motivation and enhancing study outcome at finding prime idea of students of 1 Jaken Junior High School class IX-B with SQCP learning technique. The research implementation occur in two cycles. The outcame of research: the learning process of SQCP technique run smoothly, learning motivation of students improve as the SQCP technique is applied, and the average of school grades from cycles I to cycles II are increasing to 4,59. The attainment of students from first cycle to second cycle increase to 20,83%.